The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/agronomy13020354
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Reduction in Cover Crop Vitality Followed by Pelargonic Acid Application Using Drone Imagery

Abstract: Cultivation of cover crops is a valuable practice in sustainable agriculture. In cover crop management, the method of desiccation is an important consideration, and one widely used method for this is the application of glyphosate. With use of glyphosate likely to be banned soon in Europe, the purpose of this study was to evaluate the herbicidal effect of pelargonic acid (PA) as a bio-based substitute for glyphosate. This study presents the results of a two-year field experiment (2019 and 2021) conducted in nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Due to its rapid effect, PA efficacy was higher compared with other treatments at the beginning and until 7 th day after application, but then declined over time due to the occurrence of regrowth. The findings of previous research on both annual and perennial species have demonstrated that PA reaches its maximum efficacy within several hours of application and remains effective for up to one week, although the plant regrowth subsequently reduces its efficacy (Muñoz et al, 2020;Travlos et al, 2020;Ganji et al, 2022;Muñoz et al, 2022;Pannacci et al, 2022;Ganji et al, 2023;Loddo et al, 2023).…”
Section: Discussionmentioning
confidence: 97%
“…Due to its rapid effect, PA efficacy was higher compared with other treatments at the beginning and until 7 th day after application, but then declined over time due to the occurrence of regrowth. The findings of previous research on both annual and perennial species have demonstrated that PA reaches its maximum efficacy within several hours of application and remains effective for up to one week, although the plant regrowth subsequently reduces its efficacy (Muñoz et al, 2020;Travlos et al, 2020;Ganji et al, 2022;Muñoz et al, 2022;Pannacci et al, 2022;Ganji et al, 2023;Loddo et al, 2023).…”
Section: Discussionmentioning
confidence: 97%
“…Another option is using herbicides like pelargonic acid for cover crop desiccation. Ganji et al, 2023 found it reasonably effective within a week, but further research is needed to ensure its suitability for on-farm use and to refine technical application details. Gaba et al (2018) showed that the effect of crop competition on the weed assemblage was much stronger than the effect of nitrogen fertiliser and even weed control.…”
Section: Termination Of Cover Cropsmentioning
confidence: 99%
“…Another option is using herbicides like pelargonic acid for cover crop desiccation. Ganji et al, 2023 found it reasonably effective within a week, but further research is needed to ensure its suitability for on‐farm use and to refine technical application details.…”
Section: Options For Reducing Glyphosate Use In Europementioning
confidence: 99%
See 1 more Smart Citation
“…These versatile machines, known for their stability, vertical takeoff and landing capabilities, and relatively simple mechanical structure, have become increasingly indispensable in scenarios where human intervention is either too risky or impractical. Notable for their deployment in diverse environments-ranging from the precision-required tasks in agriculture [2][3][4][5][6] to the hazardous zones of natural disasters-Quadrotors stand at the forefront of technological innovation.…”
Section: Introductionmentioning
confidence: 99%